Macro-B12 masking B12 deficiency. Issue 1 (13th January 2022) - Wolffenbuttel, Bruce H R; Muller Kobold, Anneke C; Sobczyńska‐Malefora, Agata; Harrington, Dominic J
Abstract : In clinical practice, the finding of an elevated serum B12 concentration is often the consequence of supplementation with B12 in either oral form or injections. Also, elevated serum B12 may be associated with underlying disorders, like liver diseases or a (haematologic) malignancy. Only a few studies have shown that it may also be the consequence of complex formation of B12 -vitamin binding proteins with immunoglobulins, the so-called macro-B12 . We describe a young woman who previously was diagnosed with B12 deficiency, and in whom, after cessation of B12 injection treatment, neurologic symptoms re-appeared, and despite this, repeatedly elevated serum B12 concentrations above the upper limit of the assay were found. We demonstrated that this was caused by the presence of macro-B12, which not only resulted in erroneous and longstanding elevated serum B12, but also masked her underlying B12 deficiency.